Role of green and multisensory packaging in environmental sustainability: Evidence from FMCG sector of Pakistan - Rui Dantas; Irfan Sabir; José Moleiro Martins; Muhammad Bilal Majid; Muhammad Rafiq; Jéssica Nunes Martins; Kanza Rana (Cogent Business & Management, 2023)
The primary purpose of this research is to explain the importance of a significant aspect of a sustainable environment: green packaging. Green packaging has been revealed to have an astounding effect on a sustainable environment. Misuse of carbon products negatively affects the environment and pollutes the surroundings to a great extent, for which one feasible solution is green packaging. The phenomenon has been investigated using two independent variables: green packaging and multi-sensory packaging. Consumer environmental knowledge has been used as a mediating variable, and consumer perception has been used as a moderating variable, whereas the dependent variable is ecological sustainability. Current research is quantitative, and data were collected from 302 FMCG customers through a Self-Administered questionnaire survey. The research approach was deductive, and the nature of the study was explanatory. AMOS software and the Structural Equation Modelling (SEM) technique have been used to test the proposed hypotheses. According to the study's findings, green packaging has a significant and positive effect on environmental sustainability, while multisensory packaging has a negative impact. Consumer perception positively moderates the relationship between green packaging and ecological sustainability. At the same time, consumer environmental knowledge had no mediating effect between green packaging, multisensory packaging, and ecological sustainability. This research fills the literature gap, as few studies exist on the relationship between green packaging and environmental sustainability. The mediating and moderating model has been tested for the first time in the FMCG sector of Pakistan. This study benefits manufacturers and marketers to know the importance of green packaging to enhance a sustainable environment. FMCG companies can use reusable and recyclable materials instead of substances like Plastic and Styrofoam for Packing, which is environmentally friendly and affordable for daily usage.
Keywords: 650; consumer environmental knowledge; consumer perception and sustainability; environmental sustainability; green packaging; multisensory packaging